ON THE HYPER-WIENER INDEX OF THORNY-COMPLETE GRAPH - V. S., Shigehalli (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Abstract: Let G be the graph. The Wiener Index W(G) is the sum of all distances between vertices of G, where as the Hyper-Wiener index WW(G) is defined as WW(G) = W(G) + Â In this paper we prove some general results on Hyper-Wiener Index of Thorny-Complete graphs. Mathematics Subject Classification: 05C12. Keywords: Thorny-complete graph, Wiener index and hyper-Wiener index.